Khaṣāiṣ al-Amthāl fī al-Qurān wa Aghrāḍuhā wa al-Mauḍū'āt allatī' ‘Ālajathā - Muhammad Chirzin (Al-Jami'ah Research Centre, 2004)
The Qur'an, as a guidance for human being, consists of some metaphors (amthal) which can be used by those who would think of it. Metaphor is a means of the Qur'an to convey its ideas related to any things which lead human being to a better life. Metaphor is able to describe Islamic values better and, even, as it is happened to human's daily life. Therefore, a number of Islamic scholars have studied metaphors in the Qur'an deeply and seriously as carried out by al-Hakīm al-Tarmizī, al-Mawardī, ibn Qayyim al-Jawziyya, Az Zarkaszī, as-Suyūtī and others. Knowledge about metaphor in the Qur'ān is very significant. Therefore, it is not an exaggeration when ash-Shāfi’ī states that a mujtahid should know about metaphor of the Qur'ān. This article tries to explore some opinions of Muslim scholars about metaphor in the Qur’ān with abroad view of its meaning, purposes and characteristics.